Drug-Induced Neurotoxicity Mechanisms Underlie Addiction Symptoms - Hu, Xinyi (Transactions on Materials, Biotechnology and Life Sciences, 2023)
The molecular mechanisms contributing to substance use disorder (SUD) have gained significant attention in recent years. In the last decade, people have found that addiction is hardly a decision of willpower but can be attributed to multiple molecular changes occurring in the brain after repeated drugs administration. The current research is focusing on understanding the mechanisms through which drugs administrations modify the brain and cause addicted individuals to become more susceptible to relapse. Notably, neurological impairments were found in drug addicts, suggesting potential drug-induced neurotoxicity. From studies conducted between 1992 to 2022, this paper analyzes the neurotoxicity of three commonly abused substances: methamphetamine (MA or METH), opiate, and cocaine at a cellular and molecular level, and the mechanisms through which they trigger neurotoxic effects. One shared neurotoxicity mechanism among the three substances is oxidative stress, as all drugs lead to an elevated DA level that renders oxidation feasible. Nonetheless, each substance exhibits unique mechanisms in addition to oxidative stress. For MA, additional neurotoxicity mechanisms include alteration in glutamate (Glu) and glial cells. Opiates could induce programmed cell death (apoptosis). Last but not the least, cocaine administration leads to decreased brain-derived neurotrophic factor (BDNF) and norepinephrine (NE) facilitation. By contributing to allostasis and withdrawal symptoms, these various neurotoxic effects play a crucial role in the addiction process, making addicts vulnerable to relapse.